The Effect of Grinzest Bioadditives on BBM Fuel Consumption in Mining Vehicles at PT Arutmin Indonesia Kintap - Khofifah; Fitri, Noor; Sulistia, Dona; Abraham, Ali; Aditya Dharma, Irfan; Habibullah, Marhaban; Maulana, Ibnu; Effendi, Fuad; Mauludiyah, Riskiyatul; Sukri, Qomarudin; Syahputra, Rahmat; Ila Nurhuddah, Ika (Chemistry Department, Universitas Islam Indonesia, 2024)
Mining industry activities have a very high dependence on fuel consumption. This dependence on the use of fuel is because diesel fuel is the main energy source to drive vehicle activities in the mining industry. Fuel consumption of PT. Arutmin Indonesia Tambang Kintap is around 40% of production costs. Given this substantial fuel demand, improving fuel efficiency is crucial, making fuel-saving measures essential. One approach to reducing fuel consumption involves adding bio-additives to enhance the fuel combustion process. The purpose of this study was to determine the effect of adding Grinzest bio additives to the fuel used by heavy machinery at PT. Arutmin Indonesia Tambang Kintap. The research steps include: (1) characterization of the fuel and bio additives; (2) blending fuel with Grinzest bio additives; (3) characterization of BBM-Grinzest blending; (4) testing the performance of Grinzest bioadditives on heavy machinery. The results of the study showed that Grinzest bio additives were able to reduce fuel consumption, reduce gas emission levels, and prevent rust (deposits) on the engine. The results of tests conducted by the team in the field showed that the addition of bioadditives to fuel with a ratio of 1:1000 showed a decrease in fuel consumption of around 7.4%.